Avaliação perioperatória da técnica de anestesia por tumescência em cadelas submetidas à mastectomia unilateral - Credie, Leonardo de Freitas Guimarães Arcoverde [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Tumescent anesthesia is a widely used technique in oncologic surgeries where large resection margins are necessary. This technique produces trans and postoperative analgesia, reduces surgical bleeding and facilitates tissue divulsion. The aim of this study was to establish the tumescent anesthesia technique and compare with the use of IV fentanyl in bitches submitted to unilateral mastectomy. Unilateral mastectomies were performed in 20 dogs, aging from 5 to 13 years, and weighing 13.57±9.57 kg, using a prospective, randomized, blinded and comparative design. Dogs were equally divided into two groups. Dogs from GT underwent tumescent anesthesia with 0,275% lidocaine solution and dogs from GF were treated with 2.5 mcg / kg of fentanyl IV transoperatively. Anesthesia was induced with propofol and maintained with isoflurane. Heart and respiratory rates, systolic, mean and diastolic arterial blood pressure, central venous pressure, SpO2, ETCO2, inspired and expired isoflurane concentration and temperature were measured trans-operatively and visual analogue scale for sedation and pain, Glasgow composite and Melbourne pain scales were measured postoperatively. The quality of the surgical approach, considering bleeding and ability for resection, and incidence of postoperative wound complications were investigated by the surgeon. It was concluded that tumescent anesthesia in bitches submitted to unilateral mastectomy is easy to perform in non-adhered, non-inflamed and non-ulcered mamary tumours and did not produce toxic levels of plasma lidocaine concentrations and therefore signs of intoxication. According to that this technique may be considered safe when used according to the conditions of this study. When compared to the trans-operative use of fentanyl, tumescent anesthesia reduced the inspired and expired isoflurane concentrations and improved postoperative analgesia. Tumescent anesthesia did not modify the anesthetic recovery and improved ...

A anestesia por tumescência é uma técnica empregada em cirurgias oncológicas que necessitem amplas margens de ressecção. Como características principais produz analgesia trans e pós-operatórias, reduz o sangramento cirúrgico e facilita a divulsão tecidual. O objetivo deste estudo foi estabelecer a técnica de anestesia por tumescência para mastectomia unilateral em cadelas e compará-la com o uso de fentanil intravenoso. De forma prospectiva, aleatória, encoberta e comparativa, foram realizadas cirurgias de mastectomia unilateral em 20 cadelas, com idades de 5 a 13 anos e peso médio de 13,57 ± 9,57 kg, divididas em dois grupos: GT – onde se realizou a anestesia por tumescência com solução de lidocaína a 0,275% e GF, cujos animais foram tratados com fentanil IV na dose de 2,5 mcg/kg. A anestesia foi induzida com propofol e mantida com isofluorano. Foram avaliados os parâmetros FC, PAS, PAM, PAD, PVC, f, SpO2, ETCO2, FiIso, ETIso e T no transoperatório e FC, f, T, EAVsed, EAVdor, EDGM, EDUM e estesiometria no pós-operatório. Adicionalmente foi avaliada a exequibilidade da cirurgia, quanto ao sangramento, exérese e complicações pós-operatórias concernentes à cicatrização. Conclui-se que, quando comparada ao uso trans-operatório do fentanil IV, a técnica de anestesia por tumescência para cirurgia de mastectomia unilateral em cadelas é facilmente factível em casos de tumores mamários não aderidos, inflamados ou ulcerados; reduziu a necessidade de anestésico inalatório no período trans-operatório; apresentou uma analgesia pós-operatória superior; não produziu, em nenhum animal, níveis considerados tóxicos de lidocaína plasmática para a espécie e, portanto, não causou sinais de intoxicação, o que a torna segura nas condições e concentrações aqui descritas; não alterou a recuperação anestésica e facilitou o procedimento cirúrgico, dada a redução do sangramento trans-operatório e do tempo ...
Keywords: Cão - Doenças; Mamas - Cirurgia; Mastectomia; Anestesia animal; Anestesia por condução; Lidocaina; Anestesiologia; Breast Surgery